Relevance of the plasma membrane calcium-ATPase in the homeostasis of calcium in the fetal liver - Delgado-Coello, Blanca (Organogenesis, 2015)
During the early stages of development, the embryo depends on the placenta as provider of oxygen and calcium, among other essential compounds. Although fetal liver accomplishes a well-known haematopoietic function, its contribution to calcium homeostasis upon development is poorly understood. The homeostasis of cell calcium contributes to diverse signaling pathways across developmental stages of most tissues and the calcium-ATPase located at the plasma membrane (PMCA) helps pumping excess calcium into the extracellular space. To date, the understanding of the equilibrium shift between PMCA isoforms during liver development is still missing. This review focuses on the characterization of the hepatic PMCA along the early stages of development, followed by a description of modern approaches to study calcium homeostasis involving several types of pluripotent cells. The application of interdisciplinary techniques to improve our understanding of liver development and the role calcium homeostasis plays in the definition of pathogenesis is also discussed.